2021
DOI: 10.1039/d0gc03226c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic thin film composite nanofiltration membranes derived solely from sustainable sources

Abstract: Membrane separations are considered to be sustainable technologies because of their relatively low energy consumption. However, the fabrication of membranes is yet to turn green. Thin film composite (TFC) membranes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 37 publications
(49 reference statements)
2
77
0
Order By: Relevance
“…Sustainable plant-based monomers and solvents are emerging which are alternatives to existing petroleumbased ones which are toxic and hazardous. 140 However, further research is needed to find sufficiently reactive natural monomers and suitable green solvents with compatibility for incorporation of nanomaterials.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Sustainable plant-based monomers and solvents are emerging which are alternatives to existing petroleumbased ones which are toxic and hazardous. 140 However, further research is needed to find sufficiently reactive natural monomers and suitable green solvents with compatibility for incorporation of nanomaterials.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Among them, tannic acid [76][77][78][79][80], quercetin [81], morin hydrate [82], cyclodextrin [83][84][85], chitosan [86], and vanillin [87] played a well role as a reactive material, resulting in the formation of the stable selective layer having great performance. However, most of approaches have changed only one monomer.…”
Section: Selective Layer Prepared By Sustainable Sourcesmentioning
confidence: 99%
“…Priamine having long aliphatic chains endowed high contact angle values around 100 • , leading to the outstanding permeance in non-polar solvent. To achieve the real green TFC membrane with solving the drawbacks, Park et al recently reported that the eco-friendly selective layer with 30 nm thickness was prepared with the new green monomer combination of tannic acid and Priamine using less toxic organic solvent of p-cymene instead of n-hexane as shown in Figure 9 [76]. The reaction between tannic acid and Priamine lead to the formation of C=N and C-N covalent bonds via Schiff base-based and Michael reaction-based reactions, respectively.…”
mentioning
confidence: 99%
“…Hexavalent chromium can be absorbed by the lung and gastrointestinal tract [ 36 ] and when internalized in the cells, it can react producing reactive intermediates capable to attack DNA, proteins and lipidic membranes, thereby affecting the cellular vitality and integrity. It is worth underlining and stressing that water remediation from toxic ions and compounds has developed in recent years as a hot and particularly emotive and controversial topic [ 37 , 38 , 39 , 40 ]. Most of the remediation methods regarding Cr(VI) reported in the literature are based on reduction to Cr(III) by oxidation-reduction reactions in the presence of elemental Fe, Mn(II), S 2− , organic reducing compounds and a biological approach using bacterial strain [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%